2013
DOI: 10.1002/maco.201307231
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural examination of TGO formed during pre‐oxidation on Pt‐aluminized Ni‐based superalloy

Abstract: The study concerns electron beam physical deposition (EB-PVD) of yttria stabilized zirconia (YSZ) deposited on pre-oxidized Pt-modified aluminide bond coating. The coating was prepared by the means of Pt galvanizing followed by vapor phase aluminizing at 1050 8C. During annealing at 1100 8C in air atmosphere for 4 h a 1 µm thick layer of thermally grown oxide (TGO) consisting of equiaxed a-alumina grains was formed. Focused ion beam and scanning/ transmission electron microscopy analysis revealed the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…cationic diffusion and vacancy coalescence during the initial stages of oxidation interfacial voids can form compromising the adhesion of the protective scale and leading to its premature spallation [6,[11][12][13]. In addition, free surfaces of such voids can serve as segregation sites for indigenous sulfur also weakening the adhesion of oxide scale and promoting void formation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…cationic diffusion and vacancy coalescence during the initial stages of oxidation interfacial voids can form compromising the adhesion of the protective scale and leading to its premature spallation [6,[11][12][13]. In addition, free surfaces of such voids can serve as segregation sites for indigenous sulfur also weakening the adhesion of oxide scale and promoting void formation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is thought to occur via de-lamination of the alumina scale, assisted by void formation at TiO 2 particles forming at the oxide/metal interface. Other recent investigations of the resistance of these coatings to high temperature thermal exposure [25,26] have consistently observed rutile growth on plain aluminide coatings. Shirvani et al [26] observed TiO 2 rutile formation upon plain aluminide coated CMSX-4 but not upon Pt-aluminide coated sample after cyclic oxidation.…”
mentioning
confidence: 72%
“…Como a oxidação da camada de ligação, típica dos TBC's em serviço, afeta especialmente a vida dos revestimentos, causando sua delaminação, diversos estudos vêm sendo atualmente efetuados nesta linha, buscando maior entendimento do processo em si e da variação ocasionada por este processo nas tensões e morfologia da interface [35,[58][59][60][61][62][63][64].…”
Section: Oxidação Em Alta Temperatura E Outros Fatores Adicionaisunclassified